PENGARUH VARIASITOPOGRAFIMIKRO TERHADAP VEGETASI HUTAN GAMBUT DI BENGKALIS, RIAU - Mustaid Siregar (Research Center for Biology-Indonesian Institute of Sciences, 2002)
Peat forest vegetation in Bengkalis, Riau Province was studied using plot method. Two plots of 60 m x 40 m were placed at two locations which were different in peat physical condition (Plot 1: hemofibric, > 4 m deep, inundated; and Plot 2: hemosapric, 3 m deep, rarely inundated). The results showed that there were 79 species (diameter > 2 cm) included 49 species of trees (dbh > 10 cm) and 52 species of saplings (diameter 2-9,9 cm). Total number of species in plot 1 was higher (55 species; index diversity- H'=3.048) than that of plot 2 (39 species; H'=2.606), but, density and total basal area in plot 1 was lower than that of plot 2. Species similarity index in both plots was 19%.The most dominant tree species in plot 1 were Baccaurea macrocarpa, Ficus sp. and Palaquium hexandrum, whereas in plot 2 were Calophyllum soulattri, Ganua motleyana and Palaquium burckii. The influence of physical and peat soil nutrient on structure and species composition will be discussed in this paper.